1970
DOI: 10.1128/aem.19.6.973-979.1970
|View full text |Cite
|
Sign up to set email alerts
|

Volutin Granules in Zoogloea ramigera

Abstract: Zoogloea ramigera, a gram-negative bacterium found in activated sludge, formed volutin granules when excess orthophosphate was added to a phosphate-starved culture. These volutin granules were stainable by hydrogen sulfide after lead acetate treatment and extractable by N-perchloric acid but were not adsorbed by activated charcoal. They appeared to consist of inorganic polyphosphate. Optimum granule formation in the arginine broth required 10 g of glucose, 3 mg of phosphate, and 1 to 20 mg of magnesium per lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 7 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…In wild-type HMS174(DE3) under standard GFP/LtrA induction conditions at 30 °C, 16.5% of the cells showed detectable poly(P) fluorescence localized in discrete foci, mainly at the cell poles (P), another 8.9% showed more diffuse poly(P) fluorescence (D), and the remainder (74.6%) showed no detectable poly(P) fluorescence (N), likely reflecting at least in part the sensitivity of the detection method ( Figure 6 A). The localization of poly(P) in discrete foci (“volutin granules”) at the cellular poles has been found previously in other bacteria [ 29 31 ].…”
Section: Resultssupporting
confidence: 62%
“…In wild-type HMS174(DE3) under standard GFP/LtrA induction conditions at 30 °C, 16.5% of the cells showed detectable poly(P) fluorescence localized in discrete foci, mainly at the cell poles (P), another 8.9% showed more diffuse poly(P) fluorescence (D), and the remainder (74.6%) showed no detectable poly(P) fluorescence (N), likely reflecting at least in part the sensitivity of the detection method ( Figure 6 A). The localization of poly(P) in discrete foci (“volutin granules”) at the cellular poles has been found previously in other bacteria [ 29 31 ].…”
Section: Resultssupporting
confidence: 62%
“…Zoogloea has also been involved in the oxidation of ammonia to nitrite, which is carried out by ammonium oxidizing bacteria (AOB). Furthermore, a research study conducted by Roinestad and Yall confirmed the presence of polyphosphate granules in Zoogloea cells. Polyphosphate granules are mostly detected in the PAOs cells.…”
Section: Resultsmentioning
confidence: 78%
“…Another possible explanation for the high abundance in the effluent is that these bacteria grew not only attached to the granule, but also in the bulk liquid as free floating cells. Both Meganema and Zoogloea have high substrate uptake rate and growth rate (Roinestad and Yall 1970 ; Kragelund et al 2005 ), therefore they may also grow in suspended phase even in SBRs operated at 2 min settling time and 9.3 h HRT. It has also been shown that suspended biomass can be retained under wash-out conditions if attached to the rough surfaces of broken granules (Verawaty et al 2012 ) or sheltered in indentations on the granule surface (Gonzalez-Gil and Holliger 2014 ).…”
Section: Discussionmentioning
confidence: 99%